Water Management and Cropping Patterns Optimization for Enhanced Agricultural Productivity in Sunamganj Haor Areas - Akter, T; Singha, A; Mazumder, M N N (Bangladesh Journal of Nuclear Agriculture, 2025)
Haors are bowl-shaped wetlands where water remains stagnant or experiences flash flooding between June and November. This study assessed current water management practices, cropping patterns, and associated challenges in the haor regions of Sunamganj District, using both hydro-meteorological analysis and field-based data. Primary data were collected using both qualitative and quantitative methods, including interviews and field assessments, from three Upazilas: Bishwamvarpur, Tahirpur, and Jamalgonj, involving 120 respondents. Secondary data were obtained from Upazila Administrations, Bangladesh Water Development Board, and Department of Agricultural Extension. Most respondents were farmers, and a significant portion of their cultivable land was classified as lowland. The study results show that the Rabi season is the main cropping period, while lands remain fallow during the Kharif-1 and Kharif-2 seasons due to flooding. Hydro-meteorological analysis indicates that transitioning from a single-cropping system (110–117 days) to a double-cropping pattern (174–191 days) could enhance productivity. These findings underscore the need for comprehensive technical studies on water management to assess the potential for large-scale agricultural intensification in the lowlands of the haor region, enhancing overall productivity. Bangladesh J. Nuclear Agric., 39(1): 139-153, 2025